GARDUACTION SEBAGAI PROTOTIPE BINA DAMAI BERBASIS KEARIFAN LOKAL DI DUSUN MANCINGAN, DESA PARANGTRITIS, KEC.KRETEK, KAB. BANTUL, YOGYAKARTA - Ita Fitri Astuti (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
Trash is something that is not useful anymore, discarded by the owner or the original user. In its development garbage brings negative impacts that can harm human life. In fact, the phenomenon is now actually a trigger of social conflict between community groups. The incident occurred in Hamlet Mancingan, Yogyakarta. Some of the phenomena of conflict arise because of these simple issues that cause prolonged conflict. Similarly, the conflict that has been in the name of religion. Therefore, Garduaction is one of the prototype methods of peacebuilding in Mancingan Hamlet as a community of environmentalists. In the action, Garduaction performs waste management with two principles of waste management that is reuse and recycle, such as garbage bank, education camp, little journalist, social service, and go green. These efforts can foster positive values that are linked to previously emerging values such as personal value sources, Javanese cultural values, and Islamic religious values. Keywords: History of Garduaction, Nursery Value, Emphasis Value